Credibility assessment and labelling of map mashups - Idris, Nurul Hawani (2014)
The Web 2.0 revolution has changed the culture of mapping by opening it up to a wider range of users and creators. Map mashups, in particular, are being widely used to map variety of information. There is, however, no gatekeeper to validate the correctness of the information presented. The purpose of this research was to understand better what it is that influence users’ perceived credibility and trust within a map mashup presentation and to support the future implementation of automated credibility assessment and labelling of map mashup applications. This research has been conducted in three stages using mixed method approaches. The objective of the first stage was to examine the influence of metadata related to sources, specifically the map producer and map supplier, on respondents’ assessment of the credibility of map mashup information. The findings indicate a low influence of the tested metadata and a high influence of visual cue elements on users’ credibility assessment. Only half of the respondents used the metadata whilst the other half did not include it in their assessment. These findings became the basis of stage two, which was to examine the influence of colour coded traffic light (CCTL) labelling on respondents’ assessment of credibility. From the findings, the probability of respondents making informed judgements by choosing a high credibility map based on this rating label (CCTL) was three times higher than where only the metadata was presented. The third stage was to propose a conceptual framework to support the implementation of automated credibility labelling for map mashup applications. The framework was proposed on the basis of thorough reviews from the literature. The suggested parameters and approaches are not limited to assess credibility of information in the map mashup context, but could be applied to other Web GIS applications.